2005
DOI: 10.1073/pnas.0501536102
|View full text |Cite
|
Sign up to set email alerts
|

A common haplotype in the complement regulatory gene factor H ( HF1/CFH ) predisposes individuals to age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the most frequent cause of irreversible blindness in the elderly in developed countries. Our previous studies implicated activation of complement in the formation of drusen, the hallmark lesion of AMD. Here, we show that factor H (HF1), the major inhibitor of the alternative complement pathway, accumulates within drusen and is synthesized by the retinal pigmented epithelium. Because previous linkage analyses identified chromosome 1q25-32, which harbors the factor H gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

58
1,505
9
20

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,802 publications
(1,592 citation statements)
references
References 55 publications
58
1,505
9
20
Order By: Relevance
“…In 2005, CFH and ARMS2 were identified as the major risk genes for AMD, which together have been estimated to account for over 50% of risk for developing this disease (Edwards et al, 2005;Gotoh et al, 2009;Hageman et al, 2005;Haines et al, 2005;Jakobsdottir et al, 2005;Rivera et al, 2005;Seddon et al, 2007). Subsequently, other genes associated with the complement system, namely C2/BF and C3, were also found to play a lesser role in the genetic predisposition to this condition (Gold et al, 2006;Maller et al, 2007;Yates et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2005, CFH and ARMS2 were identified as the major risk genes for AMD, which together have been estimated to account for over 50% of risk for developing this disease (Edwards et al, 2005;Gotoh et al, 2009;Hageman et al, 2005;Haines et al, 2005;Jakobsdottir et al, 2005;Rivera et al, 2005;Seddon et al, 2007). Subsequently, other genes associated with the complement system, namely C2/BF and C3, were also found to play a lesser role in the genetic predisposition to this condition (Gold et al, 2006;Maller et al, 2007;Yates et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the important role that genetic background plays in the pathogenesis of AMD was greatly enhanced in 2005, with several independent reports associating the complement factor H (CFH) gene, located on chromosome 1q31, with this disease (Edwards et al, 2005;Hageman et al, 2005;Haines et al, 2005;Klein et al, 2005). The strong association of the CFH Y402H variant allele with increased risk for AMD suggested an important role for the alternative complement pathway and the involvement of inflammation in the pathogenesis of AMD (Anderson et al, 2002;Hageman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutations are composed of a coding SNP (rs10490924) that produces the A69S mutation in the putative Age‐Related Maculopathy Susceptibility 2 (ARMS2) gene, an insertion–deletion del443ins54 that deletes the polyadenylation signal sequences of the RNA transcript, and the SNP, rs11200638, in the promoter of High Temperature Requirement A Serine Peptidase 1 ( HTRA1 ; Yang et al., 2006). The other major genetic locus linked to AMD is at chromosome 1q31, where a single nucleotide polymorphism (SNP) rs1061170 causes a missense mutation Y402H in complement factor H (CFH; Edwards et al., 2005; Klein et al., 2005; Hageman et al., 2005; Haines et al., 2005). These two genetic loci, 1q31 and 10q26, were the first to be identified in human GWAS, and they confer the most significant genetic risk of AMD alleles.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recent studies have also identified multiple genetic variants of Complement factor H (CFH), a regulator protein that can confer elevated risk of AMD. [8][9][10][11] The complement system…”
Section: Introductionmentioning
confidence: 99%